Autophagic Control of Skin Aging - Eckhart, Leopold; Tschachler, Erwin; Gruber, Florian (Frontiers in Cell and Developmental Biology, 2019)
The skin forms the barrier to the environment. Maintenance of this barrier during aging requires orchestrated responses to variable types of stress, the continuous renewal of the epithelial compartment, and the homeostasis of long-lived cell types. Recent experimental evidence suggests that autophagy is critically involved in skin homeostasis and skin aging is associated with and partially caused by defects of autophagy. In the outer skin epithelium, autophagy is constitutively active during cornification of keratinocytes and increases the resistance to environmental stress. Experimental suppression of autophagy in the absence of stress is tolerated by the rapidly renewing epidermal epithelium, whereas long-lived skin cells such as melanocytes, Merkel cells and secretory cells of sweat glands depend on autophagy for cellular homeostasis and normal execution of their functions during aging. Yet other important roles of autophagy have been identified in the dermis where senescence of mesenchymal cells and alterations of the extracellular matrix are hallmarks of aging. Here, we review the evidence for cell type-specific roles of autophagy in the skin and their differential contributions to aging.